Tehnik Reframing dalam Konseling Individu untuk Mengatasi Emosi Marah pada Siswa Di SMP Katolik Sang Timur Jakarta - Kondo, Makarius; Anas, Muhammad; Saniasa, Saniasa (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
Counseling techniques in the individual counseling approach are widely used to help overcome student problems. This study aims to describe the use of reframing techniques in individual counseling approaches to students at Sang Timur Catholic Junior High School Jakarta who have difficulty controlling angry emotions. The difficulties in overcoming angry emotions were revealed in the student needs questionnaire (AKPD) where almost 65.4% felt they had difficulty controlling their emotions. This research used a qualitative approach with a descriptive qualitative type in PPL (Field Learning Practice) activities. The results of this study indicate that fro, three cycles of individual counseling activities carried out on three students fpr 14 days with reframing techniques, it shows that clients or students can successfully control their emotions. From this study it can be concluded that the counselee or students can frame, frame, view from a different angle more positively in responding to the triggers of their angry emotions so that students can overcome and control their angry emotions in everyday life.